2015
DOI: 10.1007/s10103-015-1710-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low-level laser therapy on bone repair: a randomized controlled experimental study

Abstract: The aim of this study was to investigate the effect of low-level laser therapy (LLLT) on bone repair in femoral fractures. Sixty adult Wistar rats were randomly assigned into one of two groups: group A (ostectomy + LLLT) or group B (ostectomy + sham laser). An experimental model of complete bone fracture was surgically created by removing a 2-mm fragment from the middle third of the femoral shaft. Data were analyzed on days 8, 13, and 18 after the fracture (subgroups 1, 2, and 3). Samples were assessed for cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
0
10

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 29 publications
4
41
0
10
Order By: Relevance
“…The laser also has a positive effect on the release of cytokines and growth factors found during the various stages of bone healing [37]. The laser therapy activates osteogenic factors such as RUNX-2 and BMP-9 on bone defects [38] and increases the expression of osteocalcin [39].…”
Section: Discussionmentioning
confidence: 99%
“…The laser also has a positive effect on the release of cytokines and growth factors found during the various stages of bone healing [37]. The laser therapy activates osteogenic factors such as RUNX-2 and BMP-9 on bone defects [38] and increases the expression of osteocalcin [39].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, some studies showed that LLLT appears to stimulate mineralization in the process of new bone formation in surgically created bone defects, likely related to earlier and longer-term expression of osteocalcin and osteopontin, two proteins associated with extracellular matrix formation and osteoblast activity 24 , which is consonant with our data concerning serum levels of ALK-P. The significance of the LLLT-induced improvement in bone mineralization lies in the fact that these matrix factors contribute to the growth, shape, and size of the newly formed bone matrix 29 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, LLLT seems to be able to stimulate the bone mineralization and production [72][73][74][75][76]. The efficiency of the use of LD-LLLT for the treatment of MRONJ has already been investigated in six prospective studies (Table 5).…”
Section: Lllt For the Treatment Of Mronjmentioning
confidence: 99%